Ecological Characteristic and Health of Mangrove Forest at Tanakeke Island South Sulawesi - Heru Setiawan; Mursidin (Jurnal Penelitian Kehutanan Wallacea, 2018)
Mangrove forest at Tanakeke Island has important roles both for ecology and economy. High pressure on mangrove caused mangrove degradation in the island. Knowledge of ecological conditions and health of mangrove forest are essential for mangrove ecosystem management at the island. The study aims to determine ecological characteristics and health status of mangrove forest at Tanakeke Island, Takalar District, South Sulawesi. This study employed quantitative methods using field survey with observations using plots of 10 m x 10 m. Observation plots were located evenly all over the island. Results showed mangrove forests at Tanakeke Island consist of 11 species belong to 8 families. Shannon-Wiener diversity index reached 2.01, 1.88, and 1.18 for tree, sapling, and seedling, respectively. Importance Value Index reached 115.31, 172.11, and 108.89 for tree, sapling, and seedling, respectively, and dominated by Rhizophora stylosa at all growth levels. Structure of mangrove forest stands resembles the letter "J" inverted, which means the structure of forest stands were quite normal as a result of the good process of plant regeneration. The density reached 706 ind/ha, 4,824 ind/ha, and 23,382 ind/ha for tree, sapling, and seedling, respectively. In general, mangrove forest health levels at Tanakeke Island were categorized in low to moderate levels.